A New Approach and Analysis of Modeling the Human Body in RFID-Enabled Body-Centric Wireless Systems - Karoliina Koski; Toni Björninen; Lauri Sydänheimo; Leena Ukkonen; Yahya Rahmat-Samii (International Journal of Antennas and Propagation)
Body-centric wireless systems demand wearable sensor and tag antennas that have robust impedance matching and provide enough gain for a reliable wireless communication link. In this paper, we discuss a novel and practical technique for the modeling of the human body in UHF RFID body-centric wireless systems. What makes this technique different is that we base the human model on measured far-field response from a reference tag attached to the human body. Hereby, the human body model accounts for the encountered human body effects on the tag performance. The on-body measurements are fast, which allows establishing a catalog of human body models for different tag locations and human subjects. Such catalog would provide a ready simulation model for a wide range of wireless body-centric applications in order to initiate a functional design. Our results demonstrate that the suggested modeling technique can be used in the design and optimization of wearable antennas for different real-case body-centric scenarios.